Institutions and social action - Hausner, Jerzy (Journal of Public Governance, 2014)
The article summarizes the debates conducted within the Krakow Circle around the problems of action, institution, and social change. Its main idea is that the power of institutions is not brute force, and coercion does not constitute prevailing behavioural factor; that society is, to a certain extent, a spontaneously and voluntarily approved order which is relatively solid even though it undergoes constant change. Institutional momentum (institutionalization) is the key for the constitution and continuation of a society. In turn, freedom and autonomy of any individual action appear to be the fundamental forces driving its development.